Age-depth models for various sites on the Peru continental margin - Jens Kallmeyer (PANGAEA, 2025)
This dataset provides age-depth relationships and age models for sites at the Peru continental margin, based on various radiometric, biostratigraphic and lithostratigraphic data. In sping 2002 ODP Leg 201 revisited sites that were previously drilled during ODP Leg 112 in 1986, we combined data from both expeditions. Except for some 14C data from Leg 201 samples, most data are bio-or lithostratigraphic data or stable isotope data that provide only relatively crude minimum and maximum age estimates. Between the four ODP Leg 201 sites the number of data points and the data quality varies considerably. During SONNE Cruise SO147 several gravity cores and Multicores were dated via 14C and 210Pb measurements. While the 14C data provide relatively precise ages, the 210Pb data only provide minimum and maximum ages. We compiled these data to estimate microbial carbon turnover via sulfate reduction, those data are findable at doi:10.1594/PANGAEA.981125 and doi:10.1594/PANGAEA.981124.